Tying up Loose Ends on Agricultural and Ethnic Studies in Ecuador - Fernando García (Revista de Antropología Social, 2014)
In spite of advances in the recognition of the collective rights of indigenous nationalities and Afro-Ecuadorians, there are still processes of economic inequality and ethnic and cultural exclusion in Ecuador. For this reason, this paper take into account seven issues linked to agricultural and Ecuadorian ethnic studies developed in the last fifty years: access to land, rural labor force, ethnic and class relations, the notion of community, racism, women’s participation and the relationship between international agencies, state and social movements.